Comparison of the biomechanical differences in the occlusal movement of wild-type and BMP9 knockout mice with apical periodontitis - Peng, Mengtian; Ma, Xiaofei; Cao, Yuying; Wang, Chunjuan; Tan, Qin; Chu, Xinyue; Zhou, Pengfei; Fu, Tiwei; Liang, Panpan; Ran, Shidian; He, Tong-Chuan; Wang, Jinhua; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Apical periodontitis is a common clinical disease caused by bacteria; bacterial metabolites can cause an imbalance in bone homeostasis, bone mass reduction, and tooth loss. Bone resorption in apical periodontitis causes a concentration of stress in the tooth and periodontal tissues during occlusion, which aggravates the disease. Emerging evidence indicates that bone morphogenetic protein 9 (BMP9), also known as growth differentiation factor 2(Gdf2), may play an important role in tooth and dentoalveolar development. Herein, we investigated the role of BMP9 in the development of apical periodontitis and its effects on the biomechanics of dentoalveolar bone. Apical periodontitis models were established in five BMP9 knockout (KO) mice and five C57BL/6 WT (wild-type) mice. At baseline and 14, 28, and 42 days after modeling, in vivo micro-computed tomography analysis and three-dimensional (3D) reconstruction were performed to evaluate the apical lesion in each mouse, and confirm that the animal models were successfully established. Finite element analysis (FEA) was performed to study the stress and strain at the alveolar fossa of each mouse under the same vertical and lateral stress. FEA revealed that the stress and strain at the alveolar fossa of each mouse gradually concentrated on the tooth cervix. The stress and strain at the tooth cervix gradually increased with time but were decreased at day 42. Under the same lingual loading, the maximum differences of the stress and strain at the tooth root in KO mice were greater than those in WT mice. Thus, these findings demonstrate that BMP9 could affect the biomechanical response of the alveolar fossa at the tooth root in mice with apical periodontitis. Moreover, the effects of BMP9 on the biomechanical response of the alveolar bone may be site-dependent. Overall, this work contributes to an improved understanding of the pathogenesis of apical periodontitis and may inform the development of new treatment strategies for apical periodontitis.